IPTEKS OPINI BPK TERHADAP LAPORAN KEUANGAN PEMERINTAH PUSAT TAHUN 2017 - Pitoy, Adventia Kristin; Warongan, Jessy (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
This study aim’s to analyze and provide a description of the provision financial audit agency opinion on the central government’s financial statements. The quality of financial reports that increased from the previous year made the financial statements of the central government get an unqualified opinion. The type research used is descriptive by using qualitative data types. Data sources in this study are secondary data types and in collecting and researching documents, qualitative analysis is used. The result show that the unqualified opinion. Obtained is a manifestation of transparency and accountability in the management of state finances, the government’s efforts that are carried out maximally in improving the quality of central government financial reports are very good.Keywords : financial statement of government, statement of audit of BPK, government financial reports, unqualified opinion